2017
DOI: 10.1080/02626667.2017.1372857
|View full text |Cite
|
Sign up to set email alerts
|

Local groundwater balance model: stakeholders’ efforts to address groundwater monitoring and literacy

Abstract: Understanding groundwater systems is crucial to ensure their monitoring and protection. Global groundwater models and predictive tools exist to better understand them. In view of scarce groundwater data especially in developing countries, the question of how to model these systems and make them usable for groundwater management is crucial. Herein, we demonstrate how a transdisciplinary process can overcome the data scarcity problem and lead to the development of a Local Groundwater Balance Model (LGBM). Over 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Lopez-Maldonado et al (2017) found that, even though groundwater is currently the main source of freshwater for the population, crucial information about the state of the system, e.g., precise location, function, quality, quantity, etc., is limited and poorly understood. For example, the meaning of polluted water and an interconnected groundwater system was not apparent in the language or the imagery of the interviewees.…”
Section: Discussion: a Biocultural Approach To Cenote Conservationmentioning
confidence: 99%
See 3 more Smart Citations
“…Lopez-Maldonado et al (2017) found that, even though groundwater is currently the main source of freshwater for the population, crucial information about the state of the system, e.g., precise location, function, quality, quantity, etc., is limited and poorly understood. For example, the meaning of polluted water and an interconnected groundwater system was not apparent in the language or the imagery of the interviewees.…”
Section: Discussion: a Biocultural Approach To Cenote Conservationmentioning
confidence: 99%
“…There can be no clearer sources of information regarding the importance and sacredness of cenotes than the importance of recognizing and revitalizing ancient Maya wisdom to help protect groundwater and the society that depends on it. Thus, Lopez-Maldonado et al (2017) emphasized the importance of groundwater literacy: the knowledge of the users about the resource and its attributes, and the perception and valuation of impacts on the system. Ecology and Society 22(4): 7 https://www.ecologyandsociety.org/vol22/iss4/art7/ CONCLUSIONS Cenotes are sinkholes through which people access water from the Yucatan Peninsula Aquifer.…”
Section: Discussion: a Biocultural Approach To Cenote Conservationmentioning
confidence: 99%
See 2 more Smart Citations
“…During the dry season, rainfall is almost absent (1.4 mm) [39,40]. The hydrological unit area of the Yucatán Peninsula Aquifer includes the states of Yucatán, Campeche, and Quintana Roo [41]. It is the most extensive karstic aquifer in the world [42].…”
Section: Case Study Regionsmentioning
confidence: 99%